2012
DOI: 10.1371/journal.pone.0033946
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Khat (Catha edulis) Chewing among High School Students in Eastern Ethiopia: A Cross-Sectional Study

Abstract: BackgroundUse of psychoactive drugs such as khat leaves (Catha edulis) alter moods and emotional state and lead to adverse effects on the health and social life of users. Ethiopia is a major producer and exporter of khat in east Africa and the majority of the khat comes from the eastern part of the country, however, no studies have been conducted to investigate the habit in this area. This study was conducted to assess the prevalence and predictors of khat chewing among high school students in Harar, eastern E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
139
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(188 citation statements)
references
References 19 publications
40
139
9
Order By: Relevance
“…In our study male stu-dents currently chewed khat more than female students (Table 3). Similar differences were reported in a surveys carried out in different parts of Ethiopia and other world (Aklog et al, 2013;Negussie et al, 2014;Derese & Seme, 2014;Tilahun & Ayele, 2014;Mulugeta, 2013;Kebede, 2001;Reda et al, 2012;Gebreslassie, 2013;Abrha, 2013;Otieno & Ofulla, 2009;Alsanosy & Mutwakel, 2013;Hussien, 2009). This significant difference may be due to the cultural acceptance of male practicing unusual things including khat chewing, alcohol and other substances than females in Ethiopia and it is not an exceptional in our study area.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In our study male stu-dents currently chewed khat more than female students (Table 3). Similar differences were reported in a surveys carried out in different parts of Ethiopia and other world (Aklog et al, 2013;Negussie et al, 2014;Derese & Seme, 2014;Tilahun & Ayele, 2014;Mulugeta, 2013;Kebede, 2001;Reda et al, 2012;Gebreslassie, 2013;Abrha, 2013;Otieno & Ofulla, 2009;Alsanosy & Mutwakel, 2013;Hussien, 2009). This significant difference may be due to the cultural acceptance of male practicing unusual things including khat chewing, alcohol and other substances than females in Ethiopia and it is not an exceptional in our study area.…”
Section: Discussionsupporting
confidence: 84%
“…A study from Eastern Ethiopia (Nigussie et al, 2014) revealed that the prevalence of khat chewing among high school students to be 18.4%. Similarly a survey conducted among high school students in Eastern Ethiopia (Reda et al, 2012) showed that the prevalence was 24.2%. (Kebede, 2002) conducted a research in four colleges found in North West Ethiopia publicized that the life time and current prevalence of khat chewing was 26.7% and 17.5% respectively.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Among the top students' expressed reasons for khat use are; to get energized for study, to stay awake or avoid sleep and to increase academic performance 32,33 . Factors increasing the odds of students' khat use include; male gender, having friend chewing khat, having family members chewing khat, Muslim religion, pocket money, living alone during school age, cigarette smoking, financial freedom, parents' educational levels, living in rural area, and others 32,34,35 .…”
Section: Introductionmentioning
confidence: 99%